Best Paper Selection (Yearbook of Medical Informatics, 2018)
Roehrs A, da Costa CA, da Rosa Righi R. OmniPHR: A distributed architecture model to integrate personal health records. J Biomed Inform 2017 Jul;71:70-81 https://www.sciencedirect.com/science/article/pii/S1532046417301089?via%3DihubKlein DM, Pham K, Samy L, Bluth A, Nazi KM, Witry M, Klutts JS, Grant KM, Gundlapalli AV, Kochersberger G, Pfeiffer L, Romero S, Vetter B, Turvey CL. The veteran-initiated electronic care coordination: a multisite initiative to promote and evaluate consumer-mediated health information exchange. Telemed J E Health 2017 Apr;23(4):264-27 https://www.liebertpub.com/doi/abs/10.1089/tmj.2016.0078?url_ver=Z39.88-2003&rfr_id=ori%3Arid%3Acrossref.org&rfr_dat=cr_pub%3Dpubmed&Boockvar KS, Ho W, Pruskowski J, DiPalo KE, Wong JJ, Patel J, Nebeker JR, Kaushal R, Hung W. Effect of health information exchange on recognition of medication discrepancies is interrupted when data charges are introduced: results of a cluster-randomized controlled trial. J Am Med Inform Assoc 2017 Nov 1;24(6):1095-101 https://academic.oup.com/jamia/article-abstract/24/6/1095/3826531?redirectedFrom=fulltextDowning NL, Adler-Milstein J, Palma JP, Lane S, Eisenberg M, Sharp C; Northern California HIE Collaborative, Longhurst CA. Health information exchange policies of 11 diverse health systems and the associated impact on volume of exchange. J Am Med Inform Assoc 2017 Jan;24(1):113-22 https://academic.oup.com/jamia/article/24/1/113/2631458